Small field correction factors determination for several active detectors using a Monte Carlo method in the Elekta Axesse linac equipped with circular cones. (5th June 2019) - Girardi, Andrea; Fiandra, Christian; Giglioli, Francesca Romana; Gallio, Elena; Ali, Omar Hammad; Ragona, Riccardo
Abstract: A Monte Carlo (MC) method was used to determine small field output correction factors for several active detectors (Exradin A16, Exradin A26, PTW microLion, PTW microDiamond, Exradin W1 and IBA RAZOR) for an Elekta Axesse linac equipped with circular cones. MC model of the linac was built with the GamBet software, using the Penelope code system. The dose-to-water simulation for each cone, ranging from 5 to 30 mm of diameter size, was used to calculate field factors and the results were validated together with Gafchromic EBT3 film. Output factors (OFs) were measured with the active detectors and correction factors were determined using the MC results. The MC simulations agreed with films within 1.2%. OFs measured with Exradin W1 scintillator were in agreement within 0.8% with MC simulations. The Exradin A16 and A26 microchambers under-responded for small fields relative to the MC (−13.1% and  −4.6%, respectively). PTW microLion, IBA RAZOR and PTW microDiamond overestimated the output factor for the smallest field (+3.9%, +5.4 and  +7.1%, respectively). The present study pointed out that it is crucial to apply the appropriate correction factors in order to provide accurate measurements in small beams geometry. The results showed that the Exradin W1 can be used for very small field dosimetry without correction factors, which shall be contrariwise employed for other detectors.